Sharpen the Saw Teachers! Proposing a Model of Teacher Professional Development Program - Paulus Widiatmoko (Universitas Muhammadiyah Semarang, 2017)
Aside from their main responsibility as educators, English teachers certainly need to regularly sharpen the saw or keep improving their professionalism. These demand both understanding of theoretical foundation and practical applications of interconnected aspects of EFL teaching and learning. This paper reports a case of a teacher professional development program in reflective teaching, motivating and engaging learners, and ICT applications for language learning. These topics are chosen as they are considered essential for EFL teachers who strive for a process of building expertise. This two-day workshop elaborates experts as plenary speakers to share theoretical foundation of the three areas and teachers as parallel presenters to demonstrate good practice of their teaching experience. A quantitative assessment at the end of the training results in positive responses from the participants along with evaluations on how this model of teacher development program could be improved. As a post-workshop activity some teacher participants are assisted and facilitated to implement the material. Techniques of engaging reading and ICT use for language skill practice are chosen. Finally, six points of reflection from the committee and an external reviewer provide another assessment, evaluations, and recommendations for the program improvement.